Rejuvenation of Kajoetangan Urban Heritage Tourism area becomes an icon of Beautiful Malang destinations - Ermita Yusida; Vika Annisa Qurrata; Vidya Negeri Purnamasari; Linda Seprillina (University of Merdeka Malang, 2022)
Kampoeng Heritage Kajoetangan is one of the thematic villages in Malang City. Antiquity and historical value are the identities of this village. There are still many problems encountered through the development, there are uneven tourist spots on Dorowati Street from the observations made. Thus, it gives rise to the impression of a dualism of proper and inappropriate appearance as a tourism village. Through a service grant, the team provided a solution in the form of rejuvenating Kampoeng Heritage Kajoetangan through the manufacture of ethnic signposts and information boards for the location of standing points, location markers, and the cable installation above the Sukun River which in the process synergizes with POKDARWIS and the surrounding community to successful rejuvenation process. The results of the rejuvenation process of the Kampoeng Heritage Kajoetangan area have been carried out well with high contribution and synergy between the team, the community, and POKDARWIS in assisting the implementation of the activities in the installation of 9-point ethnic directions information boards and installation fireplaces above the Sukun River. The team hoped with rejuvenation could increase heritage village to attract more tourists after the pandemic and, in the long term, can provide a multiplier effect for the community around the heritage village.